Bookreview: Tommaso Milani (ed.): Queering language, gender, and sexuality. Sheffield: Equinox, 2018. Pp. 328. ISBN: 978-1-78-179494-4. - Meri Lindeman (Cambridge University Press, 2025)
A book note about Queering language, gender, and sexuality